IJCM_151A: Proportion of primary oesophageal cancer in persons with previous head and neck cancer in upper Assam - Devi Sagolsem Marycharan; Mahanta BN; Mahanta Tulika Goswami (Wolters Kluwer Medknow Publications, 2024)
Background: Head and neck cancer highest amongst Indian states reported from Assam and is the leading cancer in men and third leading cancer in women. Due to advanced disease at the time of diagnosis prognosis of oesophageal cancer is poor. As mass screening for oesophageal cancer is neither feasible nor reasonable, high-risk groups should be identified and surveilled. Objective: To estimate the proportion of primary oesophageal cancer in persons with previous head and neck cancer in upper Assam. Methodology: A match case-control design with equal allocation was conducted in Assam Medical College in 2017. A total of, 232 patients with head and neck squamous cell carcinoma (HNSCC) with age and gender matched controls were evaluated with chromoendoscopy for possible second malignancy in oesophagus. Structured questioning using predesigned pretested schedule was done. Data analysis was done by using rates, ratio and proportion. Results: Men women ratio of the study participants was 79.3%:20.7%(184:48). According to site of primary lesion, majority having hypo-pharyngeal lesions (33%), followed by oral cavity(25%), oropharynx(18%) and nasopharynx(4%), respectively. Out of 232 patients, 64(27.59%) showed presence of varieties of oesophageal abnormalities Conclusion: Counselling all patients and screening of high- risk group specially those with previous head and neck cancer along with health awareness creation and timely intervention may be effective in risk reduction.